PAS is a dimerization domain common to Drosophila period and several transcription factors. - Huang, Z.J.; Edery, I.; Rosbash, M. (Nature, 1993)
Mutations in the period gene product (PER) can shorten or lengthen the circadian rhythms of Drosophila melanogaster, but its biochemical activity has not been established. PER contains a motif of approximately 270 amino acids whose function is unknown (termed PAS) and which is also present in three transcription factors of the basic-helix-loop-helix (bHLH) type, in the D. melanogaster single-minded gene product (SIM), and in both subunits of the mammalian dioxin receptor complex. We show here that the PER PAS functions in vitro as a novel protein dimerization motif and that it can mediate associations between different members of the PAS protein family. The dimerization efficiency is decreased by several missense mutations in the PAS domain, including the original perL mutation, which lengthens circadian periods from 24 h to 29 h (ref. 1). The results indicate that the PAS domain may function as a dimerization domain in both SIM and the dioxin receptor complex, and that PER may regulate circadian gene transcription partly by interacting with the PAS domain of bHLH--PAS-containing transcription factors.